Przesłanie jubileuszowe dla Katedry Pedagogiki Społecznej Uniwersytetu Śląskiego w Katowicach. Ze wspomnień i refleksji - Radziewicz-Winnicki, Andrzej (Chowanna, 2019)
The author describes, from the perspective of 40th anniversary of the Department of Social Pedagogy at the University of Silesia, the period of his leadership of this scientific department in the years 1980–2010. Moreover, the author tries to characterise the activities of the Department in the era of socialism and in later years, after 1989, in the period of post-communist social changes. He expects that comparative studies will enable to find the elements of continuity and change in the last decade, when the emphasis has been placed not only at the preservation, but also at the reinforcement of the tradition of social sciences in Poland.